2002
DOI: 10.1093/genetics/162.4.1737
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Integral Membrane Desaturase Gene Family in Moths and Flies

Abstract: Lepidopteran insects use sex pheromones derived from fatty acids in their species-specific mate recognition system. Desaturases play a particularly prominent role in the generation of structural diversity in lepidopteran pheromone biosynthesis as a result of the diverse enzymatic properties they have evolved. These enzymes are homologous to the integral membrane desaturases, which play a primary role in cold adaptation in eukaryotic cells. In this investigation, we screened for desaturase-encoding sequences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…As the first step of pheromone biosynthesis, two enzymes of acetyl-CoA carboxylases (ACCs) and fatty acid synthases (FASs) are involved in the synthesis of saturated fatty acids, the precursors of sex pheromones ( Volpe & Vagelos, 1973 ; Pape, Lopez-Casillas & Kim, 1988 ; Foster & Anderson, 2012 ). Next, members of a key gene family encoding fatty acyl desaturases (FADs) determine the diversity of pheromone structures by introducing double bonds into specific positions of sex pheromones, largely contributing to the specificity of sex pheromone communication ( Hao et al, 2002 ; Knipple et al, 2002 ; Fujii et al, 2015 ; Xia et al, 2019 ). In some case, the long-chain unsaturated fatty acids are shortened by β -oxidation enzymes to further increase the diversity of species-specific pheromones ( Bjostad, Wolf & Roelofs, 1987 ).…”
Section: Introductionmentioning
confidence: 99%
“…As the first step of pheromone biosynthesis, two enzymes of acetyl-CoA carboxylases (ACCs) and fatty acid synthases (FASs) are involved in the synthesis of saturated fatty acids, the precursors of sex pheromones ( Volpe & Vagelos, 1973 ; Pape, Lopez-Casillas & Kim, 1988 ; Foster & Anderson, 2012 ). Next, members of a key gene family encoding fatty acyl desaturases (FADs) determine the diversity of pheromone structures by introducing double bonds into specific positions of sex pheromones, largely contributing to the specificity of sex pheromone communication ( Hao et al, 2002 ; Knipple et al, 2002 ; Fujii et al, 2015 ; Xia et al, 2019 ). In some case, the long-chain unsaturated fatty acids are shortened by β -oxidation enzymes to further increase the diversity of species-specific pheromones ( Bjostad, Wolf & Roelofs, 1987 ).…”
Section: Introductionmentioning
confidence: 99%
“…The C. suppressalis FAD-like genes CsupYPAQ and CsupKPSE (following the nomenclature proposed by Knipple et al [ 13 ] naming desaturase genes based on the composition of 4 amino acid residues at a signature motif) displayed 1038 nt and 1059 nt ORFs that translated into 346 and 353 aa-proteins, respectively. In a phylogenetic analysis of lepidopteran FADs, CsupYPAQ clustered into the ∆11/∆10/multifunctional FAD subfamily, whereas CsupKPSE fell into the ∆9 (C 16 >C 18 ) FAD clade (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In insects, the acyl-CoA desaturase gene family has had a very dynamic evolutionary history [ 13 , 37 , 38 ]. As a result of gene duplication bursts, many opportunities have arisen for evolution to explore protein space and produce proteins with unique and novel functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Des has been proved to play a key role in the generation of structural diversity in Lepidopteran pheromone biosynthesis because of the diverse enzymatic properties they have evolved (G. Hao et al, 2002; Liénard et al, 2010; Liu et al, 2004; H. L. Wang et al, 2010), which gives rise to divergent patterns of expression and biological roles in Lepidoptera (Knipple et al, 2002). The current study found that Ahetdes12 was abundant in the female PG transcriptome, which was consistent with the results of RT‐qPCR analysis.…”
Section: Discussionmentioning
confidence: 99%